2020
DOI: 10.1210/clinem/dgaa266
|View full text |Cite
|
Sign up to set email alerts
|

Current Management and Outcome of Pregnancies in Women With Adrenal Insufficiency: Experience from a Multicenter Survey

Abstract: Context Appropriate management of adrenal insufficiency (AI) in pregnancy can be challenging due to the rarity of the disease and lack of evidence-based recommendations to guide glucocorticoid and mineralocorticoid dosage adjustment. Objective Multicenter survey on current clinical approaches in managing AI during pregnancy. Design Retrospective anonymized da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 27 publications
3
35
1
3
Order By: Relevance
“…By suppressing ACTH production, glucocorticoids can normalise the excessive androgen production and can be used in symptomatic patients to increase fertility and during pregnancy ( 3 , 5 7 ). However, during pregnancy and especially in NCAH, most experts do not recommend dexamethasone, a category C drug that passes the placenta and has potential adverse effects on both mother and fetus ( 3 , 6 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…By suppressing ACTH production, glucocorticoids can normalise the excessive androgen production and can be used in symptomatic patients to increase fertility and during pregnancy ( 3 , 5 7 ). However, during pregnancy and especially in NCAH, most experts do not recommend dexamethasone, a category C drug that passes the placenta and has potential adverse effects on both mother and fetus ( 3 , 6 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy can be considered as a state of hypercortisolism due to general increase in the activity of the HPA-axis, and is associated with a gradual but significant increase of corticosteroid-binding globulin and total serum cortisol concentrations. During the third trimester, free cortisol concentrations rise, altogether explaining the need for higher hydrocortisone doses in AI patients (2.5 to 10mg increase of daily dose, 20 to 40% between different studies) ( 1 , 73 ). Since serum progesterone has anti-mineralocorticoid effects, fludrocortisone dose often needs also to be increased in the third trimester in patients with primary AI ( 74 ).…”
Section: Adrenal Crisis: the Most Serious And Life-threatening Manifestation Of Adrenal Insufficiencymentioning
confidence: 99%
“…Since serum progesterone has anti-mineralocorticoid effects, fludrocortisone dose often needs also to be increased in the third trimester in patients with primary AI ( 74 ). Although literature on the incidence of adrenal crisis among pregnant AI patients is scarce, a recent multicenter study of Bothou et al described the course of 128 pregnancies among 113 women with different AI etiology ( 73 ). In this report, glucocorticoid dose was increased in 57% of patients during pregnancy, whereas mineralocorticoid dose was increased only in a minority of patients.…”
Section: Adrenal Crisis: the Most Serious And Life-threatening Manifestation Of Adrenal Insufficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies of specific illnesses have suggested an association with risk of miscarriage. These include systemic lupus erythematosus [7], type 1 diabetes [8,9], celiac disease [10,11], asthma/allergies [12], thyroid disorders [13][14][15][16], Addison disease [17,18], type 2 diabetes [9,19,20], parathyroid disorders [21,22], Cushing syndrome [23], migraine [24], and epilepsy [25,26]. These scattered findings suggest that immunological, metabolic, or endocrinological mechanisms might be linked to miscarriage risk, any of which is biologically plausible since all play a role in development and function of the placenta [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%